Digital Transformation in Cashless Payment-Based Public Transportation Policy: (Service Quality Evaluation of Suroboyo Bus in Surabaya City) - Sapto Pramono; Solahuddin B Ismail; Zainal Fatah; Kristyan Dwi Djahjono; Dandy Patrija Wirawan (International Journal of Social Science and Humanity, 2024)
Digital transformation in the public transportation sector is part of the national development priority agenda aimed at improving service quality and operational efficiency. This study aims to analyze the implementation of cashless payment-based digital transformation in public transportation policy on the Suroboyo Bus in Surabaya, analyze service quality based on SERVQUAL dimensions, identify supporting and inhibiting factors for implementation, and evaluate the success and shortcomings of the policy. This research uses a qualitative approach with a descriptive research type. The results show that the implementation of cashless payment on the Suroboyo Bus has been running well since 2018, with four main payment methods: QRIS, e-money cards, plastic waste contributions, and the Child Identity Card (KIA). QRIS has become the dominant payment method with a 48% share in 2025. Service quality based on SERVQUAL dimensions shows good results in the aspects of tangibles, reliability, and responsiveness, but still requires improvement in the dimensions of assurance and empathy. Supporting factors for implementation include government commitment, the availability of regulations (Perwali No. 22 of 2023)., adequate infrastructure, and support from digital payment service providers. Inhibiting factors include limited digital literacy, internet network disruptions, limited economic access, and lack of socialization. The success of the policy is reflected in increased operational efficiency, financial transparency, and a rise in the number of users from 1.2 million (2019). to 3.5 million (2025). Shortcomings of the policy include the digital gap for vulnerable groups, dependence on internet networks, and a decrease in participation in the plastic waste payment program from 25% (2023). to 12% (2025).